2022
DOI: 10.3389/fenvs.2022.996152
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–Temporal pattern and evolutionary trend of eco-efficiency of real estate development in the yangtze river economic belt

Abstract: The eco-efficiency of real estate development (RED) is an important indicator in evaluating the effectiveness of eco-civilization construction. Thus, analyzing its temporal evolution and spatial spillover effect can help to judge the degree of coordinated development between RED and eco-civilization construction in the Yangtze River Economic Belt (YREB). From an ecology-based angle of RED, the data of 108 cities in YREB from 2006 to 2020 were selected. Then, the Super-SBM model, Moran’s I model, and Markov cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Previous studies on EE have focused on the firm (industry), regional, and national levels. For example, at the firm (industry) level, Fan et al (2022) measured the EE of real estate development using the super-SBM model and showed that the overall efficiency of 108 cities in the Yangtze River Economic Belt improved from 2006 to 2020. Zhang, Yang, Wu, et al (2022) used a similar approach to measure the EE of China's tourism industry and showed that it is generally in a stage of dynamic equilibrium.…”
Section: Eco-efficiencymentioning
confidence: 99%
“…Previous studies on EE have focused on the firm (industry), regional, and national levels. For example, at the firm (industry) level, Fan et al (2022) measured the EE of real estate development using the super-SBM model and showed that the overall efficiency of 108 cities in the Yangtze River Economic Belt improved from 2006 to 2020. Zhang, Yang, Wu, et al (2022) used a similar approach to measure the EE of China's tourism industry and showed that it is generally in a stage of dynamic equilibrium.…”
Section: Eco-efficiencymentioning
confidence: 99%